The Effect of ESG Disclosure and Firm Size on Firm Value: An Analysis Using Tobin’s Q as a Market Value Proxy Moderated by Financial Performace - Darfin Go Arianto; Sofie (Journal of Economics and Business UBS, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) performance and firm size on firm value, proxied by Tobin’s Q, among energy sector companies in Indonesia, with profitability serving as a moderating variable and leverage and firm age included as control variables. The study employed a quantitative approach using panel data from 91 energy sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period, resulting in a total of 212 observations. The data were analyzed using panel data regression, with the most appropriate model selected through the Chow, Hausman, and Lagrange Multiplier tests, indicating that the common effect model was the best-fitting model. The findings reveal that ESG has a negative and significant effect on firm value, while firm size has a positive and significant effect on firm value. Furthermore, profitability was found to strengthen the relationship between ESG and firm value but weaken the effect of firm size on firm value. These findings suggest that ESG practices have not yet been fully appreciated by the market within Indonesia’s energy sector and only generate added value when supported by strong financial performance. This study provides both theoretical and practical implications for corporate management, investors, and regulators in understanding the role of ESG in firm value creation.